Administrative Law Pragmatism - Ronald M. Levin (Washington University Journal of Law & Policy, 2011)
I decided that I would spend some time today explaining what I mean by this notion of pragmatism in the context of administrative law and how it has played out in my writing. The word “pragmatism” can have a variety of meanings, ranging from formal philosophy to popular usage. In the field of law, pragmatism commonly means a perspective that evaluates policies by looking at how they work out in practice. The test of a good policy, according to this view, is that it leads to beneficial real-world outcomes. It can be helpful to contrast pragmatism with formalism and various ideologically driven approaches: the pragmatist tends to mistrust positions that people take “on principle” if those advocates do not take account of how their positions work out in practice.
Keywords: Administrative law; Pragmatism; United States